2002
DOI: 10.1034/j.1600-0447.2002.02302.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychosis and its correlates in first‐episode psychosis in Finland and Spain

Abstract: There are universal psychosocial factors influencing DUP, but also cultural differences may have an impact on the treatment delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 44 publications
6
54
1
3
Order By: Relevance
“…Proxy measures of poor pre-morbid functioning (being single, being unemployed) and at-risk behaviour (criminal behaviour, substance use) were associated with longer delays between first psychotic symptoms and first helping contact, first treatment or first admission. These results are in accordance with the findings of previous studies exploring the characteristics associated with longer access to care (Larsen et al 1998 ;Verdoux et al 1998bVerdoux et al , 2001Norman & Malla, 2001 ;Kalla et al 2002). Poor pre-morbid functioning may delay the first helping contact attempt because subjects presenting with this characteristic are less likely to be detected and helped by their circle of relatives, friends and acquaintances than those with adequate social functioning (Cole et al 1995 ;Larsen et al 1998 ;Barnes et al 2000;Drake et al 2000).…”
Section: Interpretation Of Findingssupporting
confidence: 95%
“…Proxy measures of poor pre-morbid functioning (being single, being unemployed) and at-risk behaviour (criminal behaviour, substance use) were associated with longer delays between first psychotic symptoms and first helping contact, first treatment or first admission. These results are in accordance with the findings of previous studies exploring the characteristics associated with longer access to care (Larsen et al 1998 ;Verdoux et al 1998bVerdoux et al , 2001Norman & Malla, 2001 ;Kalla et al 2002). Poor pre-morbid functioning may delay the first helping contact attempt because subjects presenting with this characteristic are less likely to be detected and helped by their circle of relatives, friends and acquaintances than those with adequate social functioning (Cole et al 1995 ;Larsen et al 1998 ;Barnes et al 2000;Drake et al 2000).…”
Section: Interpretation Of Findingssupporting
confidence: 95%
“…Clinical data were collected from clinical records of the Outpatient Clinics for Drug Resistance at the Department of Neuroscience, including also patient family interviews, and the duration of psychosis (disease duration—DD) and the duration of untreated psychosis were calculated from the first manifestation of psychotic symptoms such as delusions, hallucinations, thought disorder, or inappropriate/bizarre behavior lasting throughout the day for several days or several times a week and requiring an unambiguous psychiatric intervention [26]. …”
Section: Methodsmentioning
confidence: 99%
“…For long-term outcome, some longitudinal studies have shown that the effect of DUP is not as great as the previously believed [11]. As regard MoO, insidious onset has been suggested to be related with unfavorable outcome [12], [13]. Accumulating evidence of these two factors (DUP and MoO) indicates that their numeric values were not only clinical usefulness, but also that onset pattern could have great effects on the etiology occurring prior to treatment intervention and further consequent disease course.…”
Section: Introductionmentioning
confidence: 98%